PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MENULIS LAPORAN PENGAMATAN SISWA KELAS V SD NEGERI 001 TELUK MAKMUR KOTA DUMAI - Amalia, Rizki; Kurniaman, Otang; Antosa, Zairul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was motivated by the low learning outcomes Indonesian students, with an average grade 69.25. While the value of maximum completeness criteria (KKM) BahasaIndonesia is 75. Among the students of 20 people, only 8 students who reach KKM with classical completeness 40%. This study is a Classroom Action Research (CAR) conducted aims to improve the ability to write reports observations Elementary School fifth grade students 001 Gulf Makmur Dumai City with implementing media use pictures. Formulation of the problem: Is the use of media images may improve the ability to write reports observations Elementary School fifth grade students 001 Gulf Makmur Dumai City? This study was conducted starting on February 9 2015 until February 28, 2015 with 2 cycles. The subjects were students of class V Elementary School 001 Makmur Gulf of Dumai City with the number of students as 20orang students as a source of data. Instrument of data collection in this paper is a sheet of activities of teacher and student activity sheets and learning outcomes. This thesis presents the results of learning derived from the value of daily tests before treatment with an average of 69.25, an increase in the first cycle with the average being 75.75. In the second cycle increased by an average of 83.5. Observation activities of teachers in the learning process in the first cycle of the first meeting and the second meeting of the 50% increase to 62.5%. Second cycle of the first meeting and the second meeting of the 66.66% increase to 83.33% on the observation of student activity in the first cycle of the first meeting and the second meeting of the 58.33% increase to 66.66%. The first meeting of the second cycle and 75% for the second meeting increased to 83.33%. Results of the study in class V Elementary School 001 Makmur Gulf of Dumai City proved that use of media images may improve the ability to write reports observations Elementary School fifth grade students 001 Gulf Makmur Dumai City.Keywords: Use of media images.